A Heuristic and Operational Continuity. Review of Franca Sinopoli and Silvia Contarini (eds.), Transculturalità: un concetto operativo in Europa? (Lithos, 2023) and of Alessandro Benucci, et al. (dir.), L’Europe trans-culturelle dans le monde global/ Transcultural Europe in the Global World (Presses Universitaires de Paris Nanterre, 2023) (ENTHYMEMA, 2023)
This contribution intends to review the two volumes Transculturalità: un concetto operativo in Europa? and L'Europe transculturelle dans le monde global/ Transcultural Europe in the Global World, results of two conferences held respectively at the Sapienza University of Rome on 27 May 2022 and at the Université Paris Nanterre on 17 and 18 November 2022 The works are part of the Transcultural Europe in the Global World (TransEu) re-search project, winner of the Jean Monnet Erasmus+ call. The objective of the initiative is to study the transcultural processes of contemporary Europe through the close dialogue of a team with a multidisciplinary and transnational horizon, so as to fully understand the hypermobility that shapes anthropic events in an acceleration and proliferation of cultural interactions.
Keywords: Transculturality; TransEu; Transnationality; Hypermobility; Postmigration